Hypopharyngeal large cell neuroendocrine carcinoma. (29th December 2015) - Lee, Wei-I; Ameratunga, Malaka; du Plessis, Justin; Gan, Hui
Abstract : Neuroendocrine carcinoma (NEC) of the head and neck is rare. We report a case of a 56-year-old man with a 6-week history of dysphagia, a neck mass and weight loss. He was diagnosed with a hypopharyngeal large cell NEC (LCNEC) with metastases to multiple sites. He received two cycles of cisplatin and etoposide. Subsequent restaging scan revealed progressive disease. The patient declined further chemotherapy and died shortly after. This is the third case of LCNEC of hypopharynx reported in the English literature and the first to progress on platinum-based chemotherapy. Although LCNEC of the head and neck is still classified as an atypical carcinoid, there is increasing evidence it is a distinct clinicohistopathological entity that carries an especially poor prognosis. Currently, there is a paucity of data to guide treatment of this rare malignancy.